2005
DOI: 10.1021/jf040325p
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Determination of Antioxidative Activity of Oligomeric Procyanidins from the Seedpod of Nelumbo nucifera Gaertn.

Abstract: The procyanidins of nonedible parts of lotus (Nelumbo nucifera Gaertn.) were determined for the first time. The procyanidins of lotus seedpod were extracted with Me(2)CO/H(2)O and purified by Sephadex LH-20 column chromatography, with a purity of >98%. ESI-MS analysis showed that the main molecular weight distribution of procyanidins ranged from 291 to 1155, with M + H peak values of 291.1, 579.2, 731.2, 867.2, 1019.4, and 1155.3, respectively. This indicates that the extract contains monomers, dimers, and tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 13 publications
2
121
0
1
Order By: Relevance
“…The seed of Nelumbo nucifera (Gaertn), also known as the lotus, is traditionally used in Chinese folk medicine. A number of previous studies have reported that the lotus seed exhibits numerous health benefits and pharmacological effects, such as anti-ischemic (11), antioxidant (12)(13)(14), hepatoprotective (12), antiproliferative (15)(16)(17)(18)(19), anti-inflammatory (20), anti-infertility (21), anti-arrhythmic (22)(23)(24)(25)(26), antifibrotic (27) and antiviral (28) activities. In the present study, the anticancer activity of alkaloids extracted from the Ba lotus seed (BLSA), a new variety of Nelumbo nucifera, which only grows in Chongqing, a city located in the southwest of China, was investigated in human NPC CNE-1 cells.…”
Section: Anticancer Activities Of Alkaloids Extracted From the Ba Lotmentioning
confidence: 99%
“…The seed of Nelumbo nucifera (Gaertn), also known as the lotus, is traditionally used in Chinese folk medicine. A number of previous studies have reported that the lotus seed exhibits numerous health benefits and pharmacological effects, such as anti-ischemic (11), antioxidant (12)(13)(14), hepatoprotective (12), antiproliferative (15)(16)(17)(18)(19), anti-inflammatory (20), anti-infertility (21), anti-arrhythmic (22)(23)(24)(25)(26), antifibrotic (27) and antiviral (28) activities. In the present study, the anticancer activity of alkaloids extracted from the Ba lotus seed (BLSA), a new variety of Nelumbo nucifera, which only grows in Chongqing, a city located in the southwest of China, was investigated in human NPC CNE-1 cells.…”
Section: Anticancer Activities Of Alkaloids Extracted From the Ba Lotmentioning
confidence: 99%
“…The roasted seeds are good coffee substitute and possess saponins, phenolics in appreciable quantities 41 . Seeds of N. nucifera consist of 10.5% moisture, 10.6-15.9% protein, 1.93-2.8% crude fat, 70-72.17% carbohydrate, 2.7% crude fibre, 3.9-4.5% ash and energy 348.45 cal/100 Minerals of lotus seeds consists of chromium (0.0042%), sodium (1%), potassium (28.5%), calcium (22.1%), magnesium (9.2%), copper (0.0463%), zinc (0.084%), manganese (0.356%) and iron (0.199%) 42,43 .…”
Section: Nutritional Value Of Lotusmentioning
confidence: 99%
“…A set of 109 representative samples of the PDO Jianning-WLS were collected from the original producing area (Jianning, Fujian) and 120 non-PDO WLS objects were collected from five main producing areas, namely, Jiangsu (26), Hunan (25), Hubei (27), Jiangxi (20), and Zhejiang (22). All the samples were harvested in 2013 and were kept with intact packaging in a cool and dark place before NIR analysis.…”
Section: Collection Of Samplesmentioning
confidence: 99%
“…It is widely cultivated in China, India, Thailand, South Korea, and Japan, as well as the US [14,15]. Recent researches have demonstrated that lotus seeds contain a variety of bioactive components (e.g., flavonoids, phospholipids, proteins, amino acids, vitamins, sugars, unsaturated fatty acids, and essential minerals) [16,17] and its extract displays significant antipyretic, cooling, astringent, antioxidant, and cytoprotective effects and demulcent properties [18][19][20]. In China, lotus seeds are a valuable functional food and are used for soups, congee, and many other dishes.…”
Section: Introductionmentioning
confidence: 99%